LANDASAN PEMIKIRAN TENTANG PEMBEBANAN JAMINAN DALAM KONTRAK PEMBIAYAAN MUDHARABAH PERSPEKTIF UU NO. 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH - Muhammad Yadi Harahap (Fakultas Hukum Universitas Kristen Indonesia, 2017)
The practice of sharia banking in Indonesia, the provision of mudharabah financing is generally followed by the provision of guarantees by business actors, since mudharabah financing contracts which are not followed by collateral are difficult to obtain mudharabah financing. Sharia banking interpreting collateral is an additional collateral for businesses managed by business actors in accordance with article 1 verse 26 of Law no. 21 of 2008 concerning Sharia Banking. For Sharia Banks Mudharabah financing guarantee is the second source of payment of capital given while the main source is the result of mudharib’s business. When the business actor fails to fulfill its obligations to the sharia bank, the guarantee can be used as an effort to anticipate the failure to pay the financing provided. The problems that form the basis of this research is what is the basis of the idea of imposition of collateral in mudharabah financing contract perspective of Law no. 21 of 2008. To analyze the above research question the author uses normative juridical research as a method so that found a comprehensive, systematic, critical, constructive and argumentative answers. Keywords: jaminan, kontrak, pembiayaan, mudharabah, UU No. 21 tahun 2008 tentang perbankan syariah.